ANALISIS KESULITAN GURU DALAM MENERAPKAN PEMBELAJARAN SAINTIFIK PADA MATA PELAJARAN IPS DI SMP NEGERI KOTA PALEMBANG - Han Shella Ningsih; Dewi Koryati; Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
This study attempts to: (1) described the difficulties of teachers in the implementation of scientific learning in social studies (IPS) in Junior High Schools Palembang, and (2) know the efforts in do teachers in overcome difficulties in the implementation of scientific learning in social studies (IPS) in Junior High Schools Palembang. This research is research of population to technique with drawal sample is sampling area. The Regions select are Ilir Barat I. In Kecamatan Ilir Barat I there are junior high schools 17 and junior high schools 33. Sample in this research was teachers social class junior high schools 17 and teachers social class junior high schools 33 the city of palembang which consisted of 14 people. Technique data collection in use is chief and interview. Test validity using formulas product moment of pearson and reliability test using formulas cronbach’s alpha. Technique analysis the data in use is analysis statistik-deskriptif who later in interpretation into the form of the percentage. The research results show that: (1) teachers in implementing learning rendering on the subjects of social class included in the category quite challenging in activities create or gather information. (2) difficulty in learning activities scientific is in overcome teachers by seeking information / the necessary data through reading books in a library and to find information with discuss fellow other teachers.